Changes of Extreme Sea Level in 1.5 and 2.0°C Warmer Climate Along the Coast of China - Feng, Jianlong; Li, Huan; Li, Delei; Liu, Qiulin; Wang, Hui; Liu, Kexiu (Frontiers in Earth Science, 2018)
Using hourly sea level data from 15 tide gauges along the Chinese coast and sea level data of three simulations of the Coupled Model Intercomparison Project Phase 5 (CMIP5), we assessed the changes and benefits of the extreme sea level of limiting warming to 1.5°C instead of 2.0°C. Observations show that the extreme sea level has risen with high confidence during the past decades along the coast of China, while the mean sea level change, especially the long-term change plays important roles in the changing process of extreme sea levels. Under the 1.5°C and 2.0°C warming scenarios, the sea level will rise with fluctuations in the future, so will the return levels of the extreme sea levels. Compared with the 1.5°C warming condition, the return levels under the 2.0°C warming condition will rise significantly at all tide gauges along the Chinese coast. The results indicate that a 0.5°C warming will bring much difference to the extreme sea levels along the coast of China. It is of great necessity to limit anthropogenic warming to 1.5°C rather than 2.0°C, as proposed by the Paris Climate Agreement, which will greatly reduce the potential risks of future flood disasters along the coast of China and is beneficial for risk response management.